(untitled) (Jurnal Teknologi (Sciences & Engineering), 2023)
The polybenzimidazole (PBI) membrane shows significant potential as an alternative membrane for high-temperature PEMFC. However, PBI membranes exhibit low proton conductivities under low humidity conditions and have drawbacks related to acid leaking and phosphoric acid degradation over 160°C. Notably, metal oxide particles exhibit a strong affinity for phosphoric acid. Therefore, titanium dioxide (TiO2) was introduced to investigate its impact on self-humidified PBI-SGO membrane at different mass ratios, utilizing a sonication technique. The hygroscopic properties of TiO2 on PBI-SGO composite membranes are tested for proton conductivity at varied temperatures (25-150 °C), acid doping levels, as well as ion exchange capacity to evaluate their potential as an electrolyte for high-temperature PEMFC application. The PBI-SGO-TiO2 with the mass ratio of 2:1.5 exhibited the highest proton conductivity (0.0128 S cm-1 at 25 ⁰C and 0.0207 S cm-1 at 150 ⁰C) and achieves a higher level of acid doping level and ion exchange capacity with a value of 10.23 ADL and 1.72 mmol g-1, respectively. The composite membranes are also physically characterized by using FTIR, XRD, and FESEM. The PBI-SGO-TiO2 (2:1.5) displayed a good distribution of TiO2 powder, thus contributing to the maximum proton conductivity value. The results of the study prove that the PBI-SGO-TiO2 composite membrane is a potential membrane for applications in HT-PEMFC.